Expression of growth-related factors in skeletal muscle of Pirarucu (Arapaima gigas) during growth - Carani, Fernanda Regina [UNESP]; Duran, Bruno Oliveira da Silva [UNESP]; Piedade, Warlen Pereira [UNESP]; Costa, Fernanda Antunes Alves da [UNESP]; Val, Vera Maria Fonseca de Almeida; Silva, Maeli Dal Pai [UNESP] (OMICS International, 2014)
The skeletal muscle of the species Arapaima gigas (pirarucu) constitutes the major edible part of the fish and is, therefore, an important protein source for human consumption. Post-natal muscle growth is regulated by the expression of myostatin as well as the Myogenic Regulatory Factors (MRFs) MyoD and myogenin. Once pirarucu reaches large size, we assume that the control of muscle growth by MRFs and myostatin occurs differentially at the initials life stages. In the present work we evaluated the morphological aspects and expression of MRF genes in skeletal muscle of pirarucu during early juvenile stage (Group A, up to 50 g, n=7), and post juvenile stages (Groups B, from 50 to 400 g, n=7; C, from 400 g to 5 kg, n=7, and D, from 5 to 9 kg, n=7). Transverse sections of red and white muscles were obtained to evaluate muscle fiber morphological and morphometric characteristics. MyoD, myogenin and myostatin genes and protein expressions were determined after quantitative real-time polymerase chain reaction and western blotting, respectively. Pirarucu skeletal muscle exhibited similar morphologies at different life stages. It was possible to conclude that both hyperplasia and hypertrophy occur during muscle growth in early and postjuvenile stages. As regard as expression, both mRNA and protein levels were similar among all groups for MyoD and myogenin. Myostatin presented lower mRNA levels and higher protein levels in early-juvenile stage, compared with the other groups. The levels of MRFs and myostatin might be involved in a balance that controls hyperplasia and hypertrophy occurring during post-natal muscle growth. Myostatin does not appear to play a crucial role during pirarucu early-juvenile stages. Since this species represents an interesting model for aquaculture programs due to high growing rates, our data suggest that the best phase to improve muscle growth in pirarucu is at post-juvenile stage and this will turn the employment of pirarucu farming economically better.
Keywords: Fish skeletal muscle; Muscle growth; 46 Myogenic regulatory factors; Myostatin; RT-qPCR; Western blotting; Pirarucu arapaima gigas